Sunspot drawings by Japanese official astronomers in 1749–1750. (11th July 2018) - Hayakawa, Hisashi; Iwahashi, Kiyomi; Fujiyama, Masashi; Kawai, Toshiki; Toriumi, Shin; Hotta, Hideyuki; Iijima, Haruhisa; Imada, Shinsuke; Tamazawa, Harufumi; Shibata, Kazunari
Abstract: Sunspot observations with telescopes in the 18 th century were carried out in Japan as well as elsewhere. One of these sunspot observations is recorded in an account called Sansaizusetsu narabini Kansei irai Jissoku Zusetsu (Charts of Three Worlds and Diagrams of Actual Observations since Kansei Era). We have analyzed manuscripts of this account to show a total of 15 sunspot drawings during 1749–1750. These observations are considered to be carried out by contemporary official astronomers in Japan, with telescopes covered by zongurasus (< zonglas in Dutch, corresponding to "sunglass" in English). We counted their group number of sunspots to locate them in long-term solar activity and show that their observations were situated near the solar maximum in 1750. We also computed their locations and areas, while we have to admit differences of the variant manuscripts with one another. These observational records show the spread of sunspot observations not only in Europe, but also in Japan, and hence may contribute to crosscheck, or possibly to improve the known sunspot indices.